The work of Raimund Abraham - Frampton, Kenneth (A+U)
Se analizan varias obras del arquitecto. Contiene: Monument to a Fallen Building, 1981. The Church on the BerlinWall, 1984. Times Theater Tower, 1984. Projects for Biennale Architettura Venezia, 1985. Projects for the International Building Exhibition Berlin, 1981-86.